Effect of calcination on serpentin crystal structure gathered form Jorong Sungai Padi, Nagari Lubuak Gadang Kecamatan Sangir, Solok Selatan - Vivi Febrini (Department of Physics – Universitas Negeri Padang UNP, 2014)
Serpentine rock alteration of olivine is widespread with content that is rich in magnesium oxide and silica. It has done research on the serpentine from Jorong Sungai Padi by giving heat treatment for investigating the crystal structure of serpentine. The samples of serpentine were crushed and sieved till form powder and calcined at temperature 725 ℃ to 825 ℃ for 1 hour. The results calcination were characterized by X-Ray Diffraction (XRD). The results calcination showed that the serpentine occurred alteration of structure, such as from monoclinic structure became orthorombic structure. That’s mean showed, in serpentine had a new minera